RETRACTED ARTICLE: Extracorporeal membrane oxygenation support for SARS-CoV-2: a multi-centered, prospective, observational study in critically ill 92 patients in Saudi Arabia - Saad Alhumaid; Abbas Al Mutair; Header A. Alghazal; Ali J. Alhaddad; Hassan Al-Helal; Sadiq A. Al Salman; Jalal Alali; Sana Almahmoud; Zulfa M. Alhejy; Ahmad A. Albagshi; Javed Muhammad; Amjad Khan; et al. (European Journal of Medical Research)
Abstract Background Extracorporeal membrane oxygenation (ECMO) has been used as a rescue strategy in patients with severe with acute respiratory distress syndrome (ARDS) due to SARS-CoV-2 infection, but there has been little evidence of its efficacy. Objectives To describe the effect of ECMO rescue therapy on patient-important outcomes in patients with severe SARS-CoV-2. Methods A case series study was conducted for the laboratory-confirmed SARS-CoV-2 patients who were admitted to the ICUs of 22 Saudi hospitals, between March 1, 2020, and October 30, 2020, by reviewing patient’s medical records prospectively. Results ECMO use was associated with higher in-hospital mortality (40.2% vs. 48.9%; p = 0.000); lower COVID-19 virological cure (41.3% vs 14.1%, p = 0.000); and longer hospitalization (20.2 days vs 29.1 days; p = 0.000), ICU stay (12.6 vs 26 days; p = 0.000) and mechanical ventilation use (14.2 days vs 22.4 days; p = 0.000) compared to non-ECMO group. Also, there was a high number of patients with septic shock (19.6%) and multiple organ failure (10.9%); and more complications occurred at any time during hospitalization [pneumothorax (5% vs 29.3%, p = 0.000), bleeding requiring blood transfusion (7.1% vs 38%, p = 0.000), pulmonary embolism (6.4% vs 15.2%, p = 0.016), and gastrointestinal bleeding (3.3% vs 8.7%, p = 0.017)] in the ECMO group. However, PaO2 was significantly higher in the 72-h post-ECMO initiation group and PCO2 was significantly lower in the 72-h post-ECMO start group than those in the 12-h pre-ECMO group (62.9 vs. 70 mmHg, p = 0.002 and 61.8 vs. 51 mmHg, p = 0.042, respectively). Conclusion Following the use of ECMO, the mortality rate of patients and length of ICU and hospital stay were not improved. However, these findings need to be carefully interpreted, as most of our cohort patients were relatively old and had multiple severe comorbidities. Future randomized trials, although challenging to conduct, are highly needed to confirm or dispute reported observations.